System rządów premierowskich jako nowy typ systemu rządów: casus Wielkiej Brytanii - SZYMANEK, Jarosław (Przegląd Politologiczny, 2018)
The paper attempts to address the question of whether the prime ministerial system has already emerged as a separate system of governance that differs from classical systems, and whether it can no longer be treated as a certain sub-class in an extensive range of parliamentary systems, but rather as a new type of system in its own right. The principal issue appears to be whether the inherent properties of the prime ministerial variety of governance are sufficiently distinct, significant and different from the parliamentary system, however broadly understood, to give the former a status of a separate governance system from the methodological point of view. It should be observed that the contemporary British system, which serves as a foundation for our deliberations on the prime ministerial form of governance, has deviated from the classical or typical parliamentary system far enough to actually take the direction of a separate system of governance, namely prime ministerial governance. Firstly, this is evidenced by the removal of the monarch from the political system and establishing executive power as a virtually one-element entity concentrated in the Cabinet, and embodied by its leader. Secondly, the figure of Prime Minister is highly emphasized as he is elected ‘under the guise of common elections’ and he successfully monopolizes the work of his entire Cabinet, becoming a certain ‘trademark’ of this Cabinet, which is well supported by the principle of joint accountability of all Cabinet members, a principle that is exceptionally strictly and consistently implemented in the British system. The ongoing politological processes that tend to presidentialize and personalize politics are only accelerating these changes and making them even more apparent. The consequence in Britain is that it is the Prime Minister who accrues the power to govern and he by no means falls under the principle of classical parliamentary systems, where the government leader is only “the first among equals”. Thirdly, the House of Commons has practically lost its controlling power over the Cabinet, as primarily evidenced in the absence of a vote of no confidence, which would serve as a tool of political accountability of executive power before the legislative, the essence of any form of parliamentary governance. Fourthly, in a highly specific, deeply endemic party system which entails that various links between government and parliament typical of the parliamentary style of democracy are de facto transferred onto the internal party stage, this to an extent also explains the relevance of the division between government and opposition, a division which is neither as clear, nor as far-reaching as in the case of other parliamentary systems. All this allows us to conclude that the British system is sufficiently different to be deemed new in comparison to a typical or classical parliamentary system. The transformations that have taken place there have gone far beyond the proper, or classical, model of parliamentary governance thus forming not only a sub-class, but a separate type (or model) of governance.